Does having a COVID-19 service in the hospital affect the anxiety state and preferences of patients applying to the urology outpatient clinic - Afandiyev, Faraj; Kubliay, Eralp (International Surgery Journal, 2025)
Background: Our aim is to investigate the effect of having a COVİD-19 service in the hospital on the anxiety level of patients applying to the urology outpatient clinic and the number of patients admitted. Methods: The study was designed as a prospective cohort study. We divided the patients into Group-1 (hospital with a COVID 19 service) and Group-2 (hospital without a COVID-19 service). State Anxiety was used to determine the anxiety status of patients in Group-1 and Group-2. Scale (STAI-I) was used. Patients were interviewed face to face. Our hospital has a COVID-19 service. The purpose of the research was explained in detail. An average interview lasted 10-15 minutes. After the data were obtained, Group-1 and Group-2 were compared in terms of anxiety, age, gender and reason for applying to the hospital. Results: The total number of patients is 313, 92 of these patients agreed to participate in the survey. The number of patients in Group 1 and Group 2 is 33 and 59, respectively. Median age is in Group 1 and Group 2, respectively. 53.03±15.98 and 47.53±15.8 (mean±SD). When we look at it in terms of anxiety, we found that the presence of the COVİD service negatively affected the psychological state of the patients. 96% (58/60) of the patients with severe anxiety applied to the urology outpatient clinic of the hospital without a COVID service (p=0.001). According to the results of multivariate analysis patients who need to start their treatment as soon as possible are more likely to apply to the urology clinic of hospitals that do not have a COVİD-19 service (odds ratio (OR): 1.284, 95% confidence interval (CI): 1.051–1.567, p=0.014). Conclusions: We believe that in future epidemic situations, separating specialized hospitals for infected patients will be more efficient both for managing the epidemic and for oncology patients.